The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1212/wnl.48.5.1427
|View full text |Cite
|
Sign up to set email alerts
|

Schizencephaly

Abstract: Schizencephaly is an uncommon congenital disorder of cerebral cortical development. Although a well-recognized cause of seizures and developmental deficits in children, previous reports describe the range of neurodevelopmental outcome in only 47 patients. We report the clinical and cranial imaging features of 47 children with unilateral open-lip (17), unilateral closed-lip (12), bilateral open-lip (12), and bilateral closed-lip (6) schizencephaly, as defined radiologically. The schizencephalic cleft occurred m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 0 publications
10
122
1
3
Order By: Relevance
“…Therefore, our data suggest that the clinical feature is also related to the presence of other central nervous system anomalies, corroborating the findings of Granata et al (13) . The clinical feature was in agreement with data reported by other authors (6,9,14,15) , with the majority of patients presenting motor deficit and neuropsychomotor development delay (8,9) . Also, we have observed that epilepsy was more frequent and severe in patients with a more significant loss of cortical area, an aspect that has not been described in the studies of Barkovich & Kjos (5) , Granata et al (14) and Denis et al…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, our data suggest that the clinical feature is also related to the presence of other central nervous system anomalies, corroborating the findings of Granata et al (13) . The clinical feature was in agreement with data reported by other authors (6,9,14,15) , with the majority of patients presenting motor deficit and neuropsychomotor development delay (8,9) . Also, we have observed that epilepsy was more frequent and severe in patients with a more significant loss of cortical area, an aspect that has not been described in the studies of Barkovich & Kjos (5) , Granata et al (14) and Denis et al…”
Section: Discussionsupporting
confidence: 92%
“…One study reported that children with unilateral schizencephaly had a mild or moderate outcome more frequently than those with bilateral lesions (62 per cent versus 28 per cent; P < 0.05). 7 Our case, however, despite having bilateral lesions, has normal development. The infant's motor system was essentially normal.…”
Section: Discussionmentioning
confidence: 54%
“…The infant only had seizures as compared to other reported cases that show more serious manifestations. 3,7 There is only one other report of a benign presentation in the presence of a significant MRI finding. 8 Prenatal ultra sonogram (USG) allows diagnosis of schizencephaly.…”
Section: Discussionmentioning
confidence: 99%
“…Defect size and location in the cortex are also important factors. 22 The presence of dysplasia and heterotopia can also contribute to a worse prognosis. 13 The prenatal diagnosis of schizencephaly and associated anomalies has an important role in prognostication and family counseling.…”
Section: Discussionmentioning
confidence: 99%